An Overview of the Industry and Handicraft in Algeria during the Ottoman Era - ben jeddou, Abdel Fattah (The Algerian Historical Journal, 2026)
This article examines the industry in Algeria during the Ottoman Era. It consists of two parts. The first deals with the biggest industries, the most important of which are: shipbuilding industry; extractive industry; railroad construction; the construction of cannons, weapons and gunpowder and building materials industry. This industry saw a great backwardness in comparison with the European countries. The second deals with the handicraft and traditional industry. We dealt with the government’s organization of the handicraft activities, then, we explained its main types. The products were excellent but were directed just to the local market.